2013
DOI: 10.5539/ass.v9n7p85
|View full text |Cite
|
Sign up to set email alerts
|

New Study Skills Training Intervention for Students Who Suffer from Test Anxiety

Abstract: This article introduced a combination of study habits and test taking skills intervention for students on how to control test anxiety and promote their abilities and academic achievement. Based on skill-deficit model, anxious students suffer from test anxiety due to inability of using sufficient study habits and test taking skills to approach examination. Study skills interventions may assist anxious students to distinguish, recover and increase their study habits and test-taking skills. Study skills training … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…Findings by Mickley Steinmetz et al (2018) show that American participants have better items and background memory compared to East Asian participants even when the congruency and the emotional intensity of the image were controlled. These findings were in line with previous findings (Ji, Peng & Nisbett, 2000;Masuda, Gonzalez & Nisbett, 2008;Motevalli et al, 2013;Stanley, Zhang, Fung, & Isaacowitz, 2013as cited in Mickley Steinmetz et al, 2018 where East Asians were more distracted with background contextual information. However, Mickley Steinmetz et al (2018) also found that there was a lack of relative evidence in differences across cultures in memory with emotion and the perception of scene incongruity.…”
Section: Adaptation Of Culture In Memory Performancesupporting
confidence: 92%
“…Findings by Mickley Steinmetz et al (2018) show that American participants have better items and background memory compared to East Asian participants even when the congruency and the emotional intensity of the image were controlled. These findings were in line with previous findings (Ji, Peng & Nisbett, 2000;Masuda, Gonzalez & Nisbett, 2008;Motevalli et al, 2013;Stanley, Zhang, Fung, & Isaacowitz, 2013as cited in Mickley Steinmetz et al, 2018 where East Asians were more distracted with background contextual information. However, Mickley Steinmetz et al (2018) also found that there was a lack of relative evidence in differences across cultures in memory with emotion and the perception of scene incongruity.…”
Section: Adaptation Of Culture In Memory Performancesupporting
confidence: 92%
“…These strategies are effective and positive strategies that can help the student in a constructive way to gain more control and to manage negative thoughts, and reduce his own anxiety through such actions. Motevalli et al [35] reported that teaching new and practical study skills helps students manage test anxiety. They found that learning some skills such as time managing for studying, properly review and summarize, how to answer multiple-choice questions, correct/incorrect and descriptive questions can control test anxiety [35].…”
Section: Discussionmentioning
confidence: 99%
“…Motevalli et al [35] reported that teaching new and practical study skills helps students manage test anxiety. They found that learning some skills such as time managing for studying, properly review and summarize, how to answer multiple-choice questions, correct/incorrect and descriptive questions can control test anxiety [35]. Yusefzadeh et al [36] reported that based on the findings of a training and evaluation program (teacher 10-35% of the final grade of the course is based on activity during the semester), the implementation of such programs significantly reduces anxiety Students are tested.…”
Section: Discussionmentioning
confidence: 99%
“…). TVET introduces students to vital knowledge and skills as it motivates them to take responsibility for their learning and outcomes, and it plays a pivotal role in ensuring that modern IR4.0 technologies are introduced to skilled workers that the industry needs (Motevalli, Roslan, Sulaiman, Hamzah, Hassan & Garmjani, 2013).…”
mentioning
confidence: 99%